ANALISIS PERILAKU KONSUMSI MAHASISWA DI E-MARKETPLACE DALAM PERSPEKTIF LITERASI KEUANGAN SYARIAH - Atok, Moh. Choirul; Ulul Maknunah, Anita (Universitas KH. A. Wahab Hasbullah, 2025)
The rapid and massive development of digital technology has changed the consumption patterns of students. This phenomenon raises concerns about excessive consumption behavior and is contrary to sharia principles, especially for students who have low sharia financial literacy. The purpose of this study is to analyze the consumption behavior of students in utilizing e-marketplaces and evaluate the role of sharia financial literacy in forming wise consumption and in accordance with Islamic values. This study uses a qualitative approach with a descriptive-analytical method through a literature review and observation of college students. The results of the study show that student consumption patterns tend to be due to trends, lifestyles, and paylater. Sharia financial literacy helps control and manage finances related to the principles of maqashid sharia and Islamic ethics. Strengthening the role of campus sharia financial institutions, educational approaches, utilization of digital media, and campus sharia communities are strategies in forming a generation of financially ethical muslims. Keywords: Consumption behavior, e-marketplace, Islamic financial literacy.